2014
DOI: 10.1093/infdis/jiu233
|View full text |Cite
|
Sign up to set email alerts
|

HIV-1 Drug Resistance in the iPrEx Preexposure Prophylaxis Trial

Abstract: Background. The iPrEx study demonstrated that combination oral emtricitabine and tenofovir disoproxil fumarate (FTC/TDF) as preexposure prophylaxis (PrEP) protects against HIV acquisition in men who have sex with men and transgender women. Selection for drug resistance could offset PrEP benefits.Methods. Phenotypic and genotypic clinical resistance assays characterized major drug resistant mutations. Minor variants with FTC/TDF mutations K65R, K70E, M184V/I were measured using 454 deep sequencing and a novel a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
66
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 69 publications
(70 citation statements)
references
References 47 publications
1
66
1
Order By: Relevance
“…Acquisition of drug-resistant HIV strains in initiators of FTC-TDF for PrEP has been documented in clinical trials. 46,47 Among participants in the FTC-TDF for PrEP treatment arm who seroconverted during the Partner's PrEP study, there were seven cases of detectable FTC-TDF-related mutations. 47 Three of those seven seroconversions were unrecognised at baseline and did not have detectable FTC-TDF-related mutations at that time, which suggests that these mutations were likely caused by treatment rather than acquisition of an already mutated strain.…”
Section: Existing and Anticipated Challenges Of The Sti Epidemic In Msmmentioning
confidence: 99%
“…Acquisition of drug-resistant HIV strains in initiators of FTC-TDF for PrEP has been documented in clinical trials. 46,47 Among participants in the FTC-TDF for PrEP treatment arm who seroconverted during the Partner's PrEP study, there were seven cases of detectable FTC-TDF-related mutations. 47 Three of those seven seroconversions were unrecognised at baseline and did not have detectable FTC-TDF-related mutations at that time, which suggests that these mutations were likely caused by treatment rather than acquisition of an already mutated strain.…”
Section: Existing and Anticipated Challenges Of The Sti Epidemic In Msmmentioning
confidence: 99%
“…These situations may increase the selection of drug-resistant mutations (DRMs), promoting spread of drug resistance and limiting future ART options through cross-resistance (25). Resistance analyses of breakthrough infections in TDF-FTC clinical trials revealed that selection of DRMs was rare in patients who became infected after receiving PrEP, but DRMs did develop in the few individuals that were HIV-1 ϩ before initiating PrEP (26)(27)(28).…”
mentioning
confidence: 99%
“…The values and ranges of the resistance parameters informed by the survey responses are presented in Tables 1 and 2. Projections associated with the M184V mutation have been used in the analysis, as this mutation is the most common mutation found in individuals that become infected despite the use of PrEP [10][11][12]. The aggregated parameter set consists of ranges representing the 90% confidence level of distributions pooled from values and ranges suggested by the experts (find pooling procedure in the S1 Text).…”
Section: Survey Results: How Virologists Describe Drug-resistance Duementioning
confidence: 99%
“…Drug resistance developed predominantly among participants with unrecognized acute HIV infection who were randomized to start PrEP. [10][11][12] Though this is somewhat reassuring, uncertainty remains regarding the resistance risk once PrEP is implemented widely; patients prescribed PrEP may not have the close monitoring and frequent HIV-testing mandated in clinical trials. As a consequence, a new HIV-infection might not be identified in a timely manner and patients who continue using PrEP may select for drug resistance.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation